Artificial Intelligence and Tomorrow’s Education - Cóndor-Herrera, Omar; Arias Flores, Hugo Patricio; Jadán Guerrero, Janio; Ramos Galarza, Carlos (My University, 2021)
Nowadays, there is a rapid technological progress around the world that has enabled realities long ago unimaginable. We live in a technological era that represents new possibilities and challenges for society, and for the educational models in each country [1]. Research on smart education, which has forced the educational community to rethink on new ways of learning and teaching has been developed globally. Due to the advent of artificial intelligence (AI), the educational model for both, teachers and students will change. Nevertheless, to transform educational systems, it is necessary to update and train students, educators, and administrators effectively [2]. This research aims to describe the possible applications of AI in education from: 1) the automation of administrative tasks; 2) collection and analysis of information [3] to create smart content; 3) the implementation of virtual assistants in the teaching-learning process; 4) the potential delivery of lectures by humanoid robots with AI. © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Competitive advantage; Energy costs; Tuna protein processor